Telework in Canada : Who Is Working from Home during the COVID-19 Pandemic ? - Chowhan, James; MacDonald, Kelly; Mann, Sara; Cooke, Gordon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2021)
SummaryThe COVID-19 pandemic has created a new reality in the world of work. Employers are realizing that to continue business operations during the pandemic they need to think differently about work : how it is organized, who does what and where the work is done. This paper addresses the question of whether there are differences in demographic and human capital characteristics between those who work from home during the pandemic and those who worked from home previously. Thus, this study takes advantage of the natural conditions of a pseudo experiment to identify the sociodemographic (i.e., sex (female/male), immigrant status, age) and human capital factors (i.e., education level, health) of those with access to telework to better understand the impact of the shutdown on these subgroups. This study uses Statistics Canada’s Canadian Perspectives Survey Series (CPSS) first survey data on the Impacts of COVID-19, and an analytic sample whose n = 2,653 ; further, the 2016 General Social Survey cycle 30 was used to provide pre-pandemic estimates for descriptive comparisons. We find that females are not less likely than males to participate in telework and that immigrant status is negatively related to work from home during the pandemic. Generally, there is support for an age relationship, with the odds of telework being relatively lower as age increases. Education level is positively associated with telework during the pandemic (e.g., having a bachelor’s or higher university degree is positively associated with telework). Finally, there is no relationship between physical or mental health and telework. This study contributes to the literature by quantifying the impact of a brief mass telework event and its implications for access to telework across sociodemographic and human capital characteristics. In a post-pandemic world, will we carry forward the lessons learned through this ‘experiment’ imposed by the pandemic ?AbstractThis study focuses on the demographic and human capital characteristics of Canadians that are associated with working from home (WFH), before and during the COVID-19 pandemic, or being absent from work, versus those Canadians who continue to work outside the home (i.e., who do not WFH). The results show significant differences in the incidence of WFH during the pandemic : 1) there are no significant differences between females and males ; 2) immigrants are less likely to WFH ; 3) younger workers are more likely to WFH ; 4) education is positively associated with WFH ; and 5) self-reported health is unrelated to WFH. The results from this natural experiment suggest potential policy and organizational implications if the pandemic WFH environment continues for an extended period of time.